2013
DOI: 10.1093/jxb/ert115
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and ethylene interact in rice grains in response to soil drying during grain filling

Abstract: This study tested the hypothesis that the interaction between polyamines and ethylene may mediate the effects of soil drying on grain filling of rice (Oryza sativa L.). Two rice cultivars were pot grown. Three treatments, well-watered, moderate soil drying (MD), and severe soil drying (SD), were imposed from 8 d post-anthesis until maturity. The endosperm cell division rate, grain-filling rate, and grain weight of earlier flowering superior spikelets showed no significant differences among the three treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 56 publications
4
94
1
1
Order By: Relevance
“…There is a report showing that water stress during the grain filling period of wheat substantially reduces grain growth rate, due to the decreased activities of AGPase and SSS (Ahmadi and Baker 2001). In contrast to the report, recent work (Chen et al 2013;Wang et al 2015) has shown that post-anthesis moderate soil drying in rice (Oryza sativa L.) could increase grain filling rate and grain weight, especially for later-flowering inferior spikelets, by enhancing activities and gene expression levels of enzymes involved in starch biosynthesis. However, how water stress or soil drying regulates carbon remobilization from stems and starch biosynthesis in grains is yet to be understood.…”
Section: Introductioncontrasting
confidence: 64%
See 1 more Smart Citation
“…There is a report showing that water stress during the grain filling period of wheat substantially reduces grain growth rate, due to the decreased activities of AGPase and SSS (Ahmadi and Baker 2001). In contrast to the report, recent work (Chen et al 2013;Wang et al 2015) has shown that post-anthesis moderate soil drying in rice (Oryza sativa L.) could increase grain filling rate and grain weight, especially for later-flowering inferior spikelets, by enhancing activities and gene expression levels of enzymes involved in starch biosynthesis. However, how water stress or soil drying regulates carbon remobilization from stems and starch biosynthesis in grains is yet to be understood.…”
Section: Introductioncontrasting
confidence: 64%
“…The mechanism involved is not clear. A probable explanation is that superior caryopses in cereals dominate over inferior ones in hormonal levels Chen et al 2013;Zhang et al 2015), and the MD treatment or the application of a low concentration of ABA in present study could not significantly alter the ABA level in superior kernels in wheat, and consequently, could not significantly affect the activities and gene expressions of the enzymes involved in starch biosynthesis in the organ. Further research is needed to understand the mechanism involved in the difference in response to soil drying and exogenous ABA application between superior and inferior caryopses in cereals.…”
Section: Discussionmentioning
confidence: 63%
“…The mechanism involved is not clear. A probable explanation is that earlier-flowering superior spikelets dominate over later-flowering inferior spikelets in hormonal levels (Yang et al 2006b;Chen et al 2013), and the MD treatment or the application of a low concentration of ABA in this study could not markedly alter the ABA biosynthesis in superior spikelets, and consequently, not significantly affect the activities and gene expressions of the enzymes in sucroseto-starch conversion in these spikelets. The mechanism underlying that the difference between superior and inferior spikelets in responses to soil drying and to exogenous ABA application needs to be further investigated.…”
Section: Discussionmentioning
confidence: 73%
“…Our earlier work (Yang and Zhang 2006;Chen et al 2013) has shown that moderate soil drying imposed during the grain filling period in rice and wheat (Triticum aestivum L.) could increase grain weight by accelerating grain filling rate, especially for later-flowering inferior spikelets. However, the mechanism in which post-anthesis moderate soil drying improves grain filling is yet to be understood.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports showing that an alternate wetting and moderate drying regime (AWMD) can significantly decrease ethylene evolution rate and increase the ratio of ABA to ethylene, and enhance the activities of key enzymes involved in sucrose to starch conversion and expressions of the genes encoding enzymes involved in starch synthesis in rice grains [44][45][46] . These processes increase the fill and weight of grain in inferior spikelets, so increasing the ratio of ABA to ethylene in grains by AWMD during grain fill is an important approach, to enhance filling of inferior spikelets.…”
Section: Improving Grain Fill In Later-flowering Inferior Spikeletsmentioning
confidence: 99%